El uso progresivo de la fuerza del servidor policial y el derecho a la integridad personal - Karla Estefanía, Moreno Ordóñez (2021)
ABSTRACT In this paper, the progressive use of force applied by police officers, its nature, antecedents and importance to comply with the purposes of public security will be analyzed, to later study the legal regulations that regulate it and its limits within the margin of right to personal integrity and deduce if these two legal institutions coexist guaranteeing the total enjoyment of a State of rights and justice. Regarding the conceptual framework, it is divided into three units: In Unit I, called public security and the integrity of people in society, the historical background, concepts and advances of public security in the international and national context are detailed. In Unit II, called personal integrity, the role of police officers is conceptualized starting from the birth of the institution of the National Police and the development that it has had within Latin America to later develop a study on the fulfillment of their functions in relation to personal integrity. Finally, in Unit III, called the excessive use of force against the right to personal integrity, the faculty of the democratic State of rights and justice is observed to be able to use force within the margin of the right to personal integrity and the analysis of a practical case in which Ecuador was sanctioned by the Inter-American Court of Human Rights, for not providing through the national legal system the progressive use of force and the mechanisms that guarantee respect for human rights recognized both in the Constitution as in international instruments. KEYWORDS: Police servants facing the progressive use of force, progressive use of force, the right to personal integrity, the rule of rights and justice. Dr. Diego Andrade Ulloa C.I. 0602051484 TUTOR